Frequency of Residential Irrigation Maintenance Problems - Michael D. Dukes; Bernard Cárdenas (EDIS)
This publication evaluates the frequency or number of times an irrigation maintenance problem occurs, as documented by Urban Mobile Irrigation Labs (UMIL) audits, and provides a list of the most common irrigation maintenance problems in residential irrigation systems. Written by Thomas R. Olmsted, Michael D. Dukes, and Bernard Cardenas, and published by the UF/IFAS Department of Agricultural and Biological Engineering, revised August 2024.